SV1. Non-invasive electrical brain stimulation in hemianopia and visual neglect. Issue 8 (August 2015) - Gall, C.
<x xml:space="preserve">Abstract</x> Non-invasive electrical brain stimulation is a promising add-on approach for neurorehabiliation of visual field loss and visual neglect. Transorbital alternating current stimulation (rtACS) has been used in clinical studies to improve visual functions in patients suffering vision loss after optic nerve damage. However, in hemianopic visual field loss the effects of rtACS are less distinct than after optic nerve damage. Combining visual field training with current stimulation may enhance training effects which has been already shown for anodal transcranial direct current stimulation (tDCS) of the occipital cortex in hemianopic visual field loss after strokes. Recent observations also indicate that rebalancing the activity between the two hemispheres as a functional mechanism accompanying recovery may be induced by lateralized respectively dual-mode tDCS application.